Thermoplastic elastomer material and preparation method thereof
By employing dynamic vulcanization technology and a dual-modal antibacterial system of ZnO@SiO2 core-shell structure loaded with ε-polylysine, combined with PNIPAM microgel, high-temperature sealing stability and long-lasting antibacterial properties of pharmaceutical packaging gasket materials are achieved. This solves the problems of poor antibacterial properties, high-temperature sealing failure, and non-degradability of traditional materials, and realizes an efficient and sustainable pharmaceutical packaging solution.
Patent Information
- Application Number
- CN202511410883.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2026-01-09
AI Technical Summary
Existing pharmaceutical packaging gasket materials have significant shortcomings in terms of antibacterial durability, high-temperature sealing stability, and environmental sustainability, making it difficult to meet the technical requirements of high-end pharmaceutical packaging.
A biodegradable island structure is constructed using dynamic vulcanization technology. Combined with a dual-modal antibacterial system of ZnO@SiO2 core-shell structure loaded with ε-polylysine, PNIPAM microgel is introduced to achieve temperature-sensitive sealing. An adaptive seal is formed by cross-linking biodegradable polyester and polypropylene, which enhances antibacterial performance and environmental friendliness.
It achieves a sealing strength retention rate of ≥95% after high-temperature sterilization, and an antibacterial effect of ≥94% after 28 days. The material is stable during its service life and is biodegradable after disposal, meeting the requirements of green manufacturing.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and specifically discloses a thermoplastic elastomer material and its preparation method. Background Technology
[0002] With the increasing demands for safety, functionality, and sustainable development in the pharmaceutical packaging industry, pharmaceutical packaging gaskets, as key components that directly contact pharmaceutical products, have material properties that directly affect drug stability, sterility, and environmental impact. Currently, pharmaceutical gasket materials mainly utilize a blend system of polypropylene (PP) and styrene-ethylene-butene-styrene block copolymer (SEBS), supplemented with butyl rubber (IIR) or silicone rubber (VMQ) as elasticity to achieve good sealing and chemical resistance. However, existing material systems still face multiple technical bottlenecks in practical applications, making it difficult to meet the increasingly stringent technical requirements of high-end pharmaceutical packaging.
[0003] First, insufficient antibacterial properties are a significant drawback of current pharmaceutical packaging pad materials. To prevent microbial contamination, traditional materials often rely on chemical antibacterial agents such as silver ions and quaternary ammonium salts for modification. However, these antibacterial agents suffer from problems such as easy migration, uneven release, and short-lasting antibacterial effects, with their antibacterial efficacy significantly diminishing after long-term use. More seriously, when facing high-risk microorganisms such as drug-resistant strains (e.g., methicillin-resistant Staphylococcus aureus, MRSA), existing antibacterial systems have limited inhibitory efficiency, failing to provide continuous and reliable bioprotection and posing a potential risk of drug contamination.
[0004] Secondly, the risk of seal failure during high-temperature sterilization limits the application of materials in aseptic packaging. Pharmaceutical packaging materials need to undergo high-temperature steam sterilization at 121°C. However, there is a difference in the coefficient of thermal expansion between the PP / SEBS blend system and rubber materials. During repeated thermal cycling, internal stress relaxation can easily occur, leading to micro-deformation or delamination of the sealing interface, which in turn can cause leakage of the drug solution or microbial invasion. In addition, traditional elastomers such as butyl rubber require vulcanization cross-linking processes to impart elasticity. This process is energy-intensive, has low production efficiency, and the cross-linked structure makes the material difficult to recycle and reuse, which is inconsistent with the development trend of green manufacturing.
[0005] Finally, poor environmental friendliness has become a key obstacle to the sustainable development of traditional pharmaceutical packaging materials. Polypropylene, as the main matrix material, is a non-biodegradable petroleum-based plastic. After disposal, it usually needs to be incinerated, which not only consumes energy but may also release harmful gases such as carbon dioxide and dioxins, exacerbating environmental pollution. At the same time, traditional rubber materials have complex cross-linked structures, resulting in high recycling costs and technical difficulties, and an extremely low overall recycling rate, which runs counter to the global "plastic reduction" strategy and the concept of a circular economy.
[0006] In summary, existing pharmaceutical packaging gasket materials have significant shortcomings in terms of antibacterial durability, high-temperature sealing stability, and environmental sustainability, and there is an urgent need to develop a new type of thermoplastic elastomer material. Summary of the Invention
[0007] To address the shortcomings of traditional thermoplastic elastomers, this invention provides a biodegradable thermoplastic elastomer for pharmaceutical packaging materials with temperature-sensitive adaptive sealing and long-lasting antibacterial functions, as well as its preparation method. This solves the technical problems of poor antibacterial properties, short antibacterial duration, high-temperature sealing failure, and non-degradability of traditional thermoplastic elastomers.
[0008] This invention is achieved through the following technical solution: A thermoplastic elastomer material comprises, by weight, the following components: 40-60 parts polypropylene, 20-30 parts styrene-ethylene-butene-styrene block copolymer, 5-15 parts biodegradable polyester, 1-3 parts antibacterial component, 3-8 parts poly(N-isopropylacrylamide) microgel, 2-5 parts cellulose nanocrystals, 1-3 parts fluorosilicone modified acrylate, 2-5 parts maleic anhydride grafted polypropylene, 10-20 parts white oil, and 0.5-1 parts natural antioxidant; wherein the antibacterial component is ZnO@mesoporous SiO2 core-shell structure supported on ε-polylysine.
[0009] The mechanism of action of the thermoplastic elastomer material of the present invention is as follows: Using polypropylene (PP), styrene-ethylene-butene-styrene block copolymer (SEBS), and biodegradable polyester (PBAT) as matrices, a biodegradable island structure is constructed through dynamic vulcanization technology. Specifically, biodegradable polyester and polypropylene form an island structure through dynamic vulcanization, with the biodegradable polyester as the dispersed phase and polypropylene as the continuous phase. The two phases are interfacially compatible through maleic anhydride grafting onto polypropylene, significantly suppressing phase separation and improving phase stability. Crosslinking of biodegradable polyester and polypropylene effectively induces crazes and shear bands, absorbing impact energy and significantly toughening the PP matrix, allowing the material to possess both the rigidity of PP and the toughness of SEBS / PBAT. Dynamic vulcanization prevents phase coarsening during subsequent processing (extrusion) and use, ensuring performance stability.
[0010] By introducing poly(N-isopropylacrylamide) (PNIPAM) microgels and cellulose nanocrystals, temperature-sensitive sealing and mechanical properties are enhanced respectively. The cross-linked network formed by dynamic vulcanization can physically encapsulate and anchor the PNIPAM microgels and cellulose nanocrystals, preventing them from migrating or leaching during multiple thermal cycles.
[0011] By combining a dual-modal antibacterial system formed by loading ε-polylysine onto a ZnO@SiO2 core-shell structure, the antibacterial properties of thermoplastic elastomers are enhanced. The cross-linked network formed by dynamic vulcanization can firmly "lock" the ZnO@SiO2 core-shell structure loaded with ε-polylysine within the elastomer phase, greatly reducing the migration and loss of antibacterial components. ZnO and SiO2 have extremely high thermal stability, easily withstanding the high temperatures during SEBS / PP blending and subsequent high-temperature and high-pressure sterilization (121℃), without any attenuation of antibacterial properties due to heat treatment. Furthermore, the thermal stability of ε-polylysine is enhanced after loading, significantly improving the reliability and durability of the antibacterial properties.
[0012] PNIPAM microgels, acting as a smart switch, combine the phase change behavior of PP with the rigid support and SEBS with the elastic recovery. During high-temperature sterilization (temperatures far exceeding LCST), PNIPAM contracts dramatically, generating strong shrinkage stress. This stress, combined with the property of PP softening upon heating (while still maintaining its shape), creates a strong "self-tightening" pressure at the sealing interface, ensuring absolute sealing reliability during sterilization. Upon cooling to room temperature (temperatures below LCST), PNIPAM re-swells. The high elasticity of SEBS ensures that the material can recover its deformation following the expansion of PNIPAM, avoiding permanent set (compression set) and achieving adaptive re-closure of the seal. The material of this invention achieves an active response of "stronger high-temperature sealing and intelligent re-sealing after cooling," far exceeding the reliability of traditional passive sealing materials. Furthermore, antibacterial components form the first line of defense within the material, inhibiting the growth of microorganisms throughout the product's lifecycle. The shrinkage and densification of PNIPAM at high temperatures further blocks the intrusion of steam and microorganisms during sterilization, forming a second physical line of defense. The two work together to provide dual protection for the contents (such as pharmaceuticals and sterile medical devices), and are suitable for biopharmaceutical packaging that requires high-temperature sterilization, such as injection stoppers and infusion bags.
[0013] Throughout the product's lifespan, PP and SEBS provide excellent durability and chemical stability, ensuring product functionality. When the product is discarded and placed in specific environments such as industrial composting, microorganisms preferentially attack the ester bonds of biodegradable polyester (PBAT). The degradation of PBAT disrupts the structural integrity of the material, creating more pores and defects, thereby exposing more PP and SEBS surfaces. Ultimately, this promotes the disintegration and biodegradation of the entire component, achieving a perfect balance between stability during its service life and biodegradability after disposal.
[0014] Preferably, the fluorosilicone-modified acrylate is a block copolymer of fluorinated acrylate and polysiloxane, with a molecular weight of 5000-10000 g / mol and a fluorine content of 15-25 wt%. The polypropylene is a copolymer of a small amount of ethylene and propylene, with a melt flow rate of 5-20 g / 10 min.
[0015] Preferably, the white oil is a mixture of C16-C31 normal and isoalkanes with a viscosity range of 10-70 mm. 2 White oil can reduce melt viscosity, improve processing fluidity, and promote the dispersion of components to form a homogeneous structure. White oil can soften and toughen, and adjust the hardness and modulus of elastomers. Furthermore, the addition of white oil makes SEBS segments more extended, enhancing the mobility of the molecular chains and making it easier for the crosslinking agent to contact the reaction sites on the molecular chains, thus improving the efficiency and uniformity of the crosslinking reaction. At the same time, it reduces the viscosity of the "island" phase, making it easier to refine into small, uniform particles under shear force, thereby forming a more stable and refined phase morphology.
[0016] Preferably, the biodegradable polyester comprises polybutylene terephthalate; the natural antioxidant comprises one or more of tea polyphenols and vitamin E.
[0017] Preferably, the preparation method of the antibacterial component includes: 1) ultrasonically dispersing nano-zinc oxide particles in an aqueous ethanol solution with a volume ratio of ethanol to water of 3:1, adding silane coupling agent KH550, reacting at 60°C for 2 hours, centrifuging and washing, and vacuum drying to obtain modified nano-zinc oxide particles; dissolving the modified nano-zinc oxide particles in an ethanol-ammonia solution with an ammonia concentration of 0.5 mol / L, adding tetraethyl orthosilicate dropwise at 60°C for 3 hours, washing three times with ethanol and deionized water, and vacuum drying to obtain ZnO@mesoporous SiO2 core-shell powder; 2) dissolving ε-polylysine in a phosphate buffer solution (pH=7.4), adding ZnO@mesoporous SiO2 core-shell powder, stirring and reacting at 30°C for 4 hours, and achieving covalent loading of ε-polylysine in the ZnO@mesoporous SiO2 core-shell structure through Schiff base reaction to obtain ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine.
[0018] Preferably, the poly(N-isopropylacrylamide) microgel has a particle size of 50-200 nm and a phase transition temperature of 32-37°C. At this phase transition temperature, the material is in a swollen state during room temperature storage and transportation, maintaining a gentle sealing pressure and avoiding excessive compression of the contents. Even during brief contact with human skin or high-temperature environments, when the temperature approaches or slightly exceeds the minimum critical melting temperature (LCST), PNIPAM will begin to shrink slightly, further strengthening the seal and preventing leakage.
[0019] A method for preparing a thermoplastic elastomer material includes the following steps: (1) Premixed material mixing: Styrene-ethylene-butene-styrene block copolymer, biodegradable polyester, cellulose nanocrystals and white oil are added to a mixer and mixed at 160-170℃ for 10-15 min to obtain premixed rubber compound; (2) Dynamic vulcanization blending: The premixed rubber compound, polypropylene, maleic anhydride-grafted polypropylene and poly(N-isopropylacrylamide) microgel are added to a twin-screw extruder. The temperature is controlled in stages: zone 1 170-175℃, zone 2 180-185℃, zone 3 175-180℃, and the screw speed is 250-350 rpm. A crosslinking agent (diisopropylbenzene peroxide) is added for dynamic vulcanization. The amount of crosslinking agent is 0.1-0.3% of the mass of the styrene-ethylene-butene-styrene block copolymer. Dynamic vulcanization takes 3-5 minutes, and the degree of vulcanization is controlled at 30-50%. (3) Functional additive blending: After ultrasonic dispersion of antibacterial components, fluorosilicone modified acrylate and natural antioxidants for 30 min, they are injected into the end of the twin-screw extruder through the side feed port and blended with the matrix; (4) The blend material obtained in step (3) is extruded through a die and placed in a cooling water tank below 40°C. It is then pelletized and dried to obtain thermoplastic elastomer granules.
[0020] The technical solution of the present invention has at least the following advantages and beneficial effects: 1. High-temperature sealing performance. Compared with traditional styrene-ethylene-butene-styrene block copolymer / polypropylene materials, the product of this invention retains ≥95% of its sealing strength after high-temperature sterilization.
[0021] 2. Antibacterial Properties. Compared to single or blended antibacterial agents, the ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine antibacterial components achieves synergistic antibacterial effects through the core-shell structure. Nano-zinc oxide generates reactive oxygen species through photocatalysis, disrupting microbial cell membranes. Simultaneously, Zn... 2+ It releases substances that interfere with bacterial metabolism. Furthermore, the core-shell structure has a high specific surface area, enabling efficient loading of ε-polylysine. ε-polylysine adsorbs onto the negatively charged bacterial membrane via cation interaction, disrupting its integrity. The core-shell structure also prolongs the antibacterial activity period, achieving a sustained antibacterial effect; the antibacterial rate remains ≥94% after 28 days. Moreover, the SiO2 shell can reduce Zn... 2+ Direct contact reduces cytotoxicity.
[0022] 3. Environmental friendliness. Biodegradable polyester and polypropylene form degradable microdomains through dynamic vulcanization, with a degradation rate of ≥60%.
[0023] 4. Surface Residue Prevention. Fluorosilicone modifiers improve the water contact angle of the material surface, with a water contact angle ≥150°, effectively reducing the risk of chemical residue. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0025] Example 1 This embodiment provides a thermoplastic elastomer material, comprising, by weight parts: matrix material: 50 parts polypropylene, 25 parts styrene-ethylene-butene-styrene block copolymer, 10 parts biodegradable polyester; functional additives: 3 parts antibacterial component (ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine), 5 parts poly(N-isopropylacrylamide) microgel, 3 parts cellulose nanocrystals, 1 part fluorosilicone modified acrylate, 4 parts maleic anhydride grafted polypropylene, 15 parts white oil, and 0.8 parts natural antioxidant.
[0026] Fluorosilicone-modified acrylate is a block copolymer of fluorinated acrylate and polysiloxane, with a molecular weight of 8000 g / mol and a fluorine content of 20 wt%. The white oil is a mixture of C16-C31 normal and isoalkanes with a viscosity range of 50 mm. 2 / s. The biodegradable polyester is polybutylene terephthalate (PET). The natural antioxidant is tea polyphenols. The poly(N-isopropylacrylamide) microgel has a particle size of 100 nm and a phase transition temperature of 35 °C.
[0027] Preparation of antibacterial components: 1) The nano-zinc oxide particles were ultrasonically dispersed in an aqueous ethanol solution with a volume ratio of ethanol to water of 3:1. Silane coupling agent KH550 was added, and the mixture was reacted at 60°C for 2 hours. After centrifugation and washing, the mixture was vacuum dried to obtain modified nano-zinc oxide particles. The modified nano-zinc oxide particles were dissolved in an ethanol-ammonia solution with an ammonia concentration of 0.5 mol / L. Tetraethyl orthosilicate was added dropwise at 60°C and reacted for 3 hours. The mixture was then washed three times with ethanol and deionized water, and vacuum dried to obtain ZnO@mesoporous SiO2 core-shell powder. 2) Dissolve ε-polylysine in phosphate buffer solution (pH=7.4), add ZnO@mesoporous SiO2 core-shell powder, stir and react at 30℃ for 4h. ε-polylysine is covalently loaded into ZnO@mesoporous SiO2 core-shell through Schiff base reaction, thus obtaining ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine.
[0028] Preparation of thermoplastic elastomer materials: (1) Premixed material mixing: Styrene-ethylene-butene-styrene block copolymer, biodegradable polyester, cellulose nanocrystals and white oil are added to a mixing mill and mixed at 160°C for 10 min to obtain premixed rubber compound; (2) Dynamic vulcanization blending: The premixed rubber compound, polypropylene, maleic anhydride-grafted polypropylene and poly(N-isopropylacrylamide) microgel were added to a twin-screw extruder. The temperature was controlled in stages: 170℃ in zone 1, 180℃ in zone 2 and 175℃ in zone 3. The screw speed was 250 rpm. A crosslinking agent (diisopropylbenzene peroxide) was added for dynamic vulcanization. The amount of crosslinking agent was 0.1% of the mass of the styrene-ethylene-butene-styrene block copolymer. Dynamic vulcanization was carried out for 3 minutes, and the degree of vulcanization was controlled at 40%. (3) Functional additive blending: ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine, fluorosilicone modified acrylate and natural antioxidants are ultrasonically dispersed for 30 min and then injected into the end of the twin-screw extruder through the side feed port to blend with the matrix; (4) The blend material obtained in step (3) is extruded through a die and placed in a cooling water tank below 40°C. It is then pelletized and dried to obtain thermoplastic elastomer granules.
[0029] Example 2 This embodiment provides a thermoplastic elastomer material, comprising, by mass parts: matrix material: 55 parts polypropylene, 28 parts styrene-ethylene-butene-styrene block copolymer, and 8 parts biodegradable polyester; functional additives: 3 parts antibacterial component (ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine), 4 parts poly(N-isopropylacrylamide) microgel, 4 parts cellulose nanocrystals, 2 parts fluorosilicone modified acrylate, 2 parts maleic anhydride grafted polypropylene, 10 parts white oil, and 1 part natural antioxidant. The preparation method is the same as in Example 1.
[0030] Fluorosilicone-modified acrylate is a block copolymer of fluorinated acrylate and polysiloxane, with a molecular weight of 10000 g / mol and a fluorine content of 25 wt%. The white oil is a mixture of C16-C31 normal and isoalkanes with a viscosity range of 70 mm. 2 / s. The biodegradable polyester is polybutylene terephthalate (PET). The natural antioxidant is vitamin E. The poly(N-isopropylacrylamide) microgel has a particle size of 200 nm and a phase transition temperature of 37 °C.
[0031] Example 3 This embodiment provides a thermoplastic elastomer material, comprising, by weight parts: matrix material: 45 parts polypropylene, 20 parts styrene-ethylene-butene-styrene block copolymer, and 15 parts biodegradable polyester; functional additives: 3 parts antibacterial component (ZnO@mesoporous SiO2 core-shell structure loaded with ε-polylysine), 3 parts poly(N-isopropylacrylamide) microgel, 5 parts cellulose nanocrystals, 3 parts fluorosilicone modified acrylate, 2 parts maleic anhydride grafted polypropylene, 10 parts white oil, and 0.5 parts natural antioxidant. The preparation method is the same as in Example 1.
[0032] Fluorosilicone-modified acrylate is a block copolymer of fluorinated acrylate and polysiloxane, with a molecular weight of 5000 g / mol and a fluorine content of 15 wt%. White oil is a mixture of C16-C31 normal and isoalkanes with a viscosity range of 10 mm. 2 / s. The biodegradable polyester is polybutylene terephthalate (PET). Natural antioxidants include tea polyphenols and vitamin E in a 1:2 mass ratio. The poly(N-isopropylacrylamide) microgel has a particle size of 50 nm and a phase transition temperature of 32 °C.
[0033] Comparative Example 1 The difference between this comparative example and Example 1 is that no poly(N-isopropylacrylamide) microgel was added, and the preparation method was the same as in Example 1.
[0034] Comparative Example 2 The difference between this comparative example and Example 1 is that the antibacterial components are replaced with nano zinc oxide and ε-polylysine, and the mass ratio of the two is 2:1. The preparation method is the same as that in Example 1.
[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that the fluorosilicone modified acrylate is replaced with ordinary acrylate, and the preparation method is the same as in Example 1.
[0036] Performance tests were conducted on the thermoplastic elastomer materials provided in the examples and comparative examples, and the results are shown in Table 1.
[0037] Table 1
[0038] As shown in Table 1, compared with Comparative Examples 1-3, the thermoplastic elastomer materials prepared in Examples 1-3 have better retention rate of sealing strength after sterilization, better antibacterial rate after 28 days, and better water contact angle, while also having a better degradation rate.
[0039] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A thermoplastic elastomer material, characterized in that, The thermoplastic elastomer comprises the following components by mass fraction: polypropylene 40-60 parts, styrene-ethylene-butylene-styrene block copolymer 20-30 parts, biodegradable polyester 5-15 parts, antibacterial component 1-3 parts, poly(N-isopropyl acrylamide) microgel 3-8 parts, cellulose nanocrystal 2-5 parts, fluorosilicon modified acrylate 1-3 parts, maleic anhydride grafted polypropylene 2-5 parts, white oil 10-20 parts, and natural antioxidant 0.5-1 part; the antibacterial component is ZnO@mesoporous SiO2core-shell structure loaded with ε-polylysine.
2. The thermoplastic elastomer material according to claim 1, characterized in that, The fluorosilicon modified acrylate is a block copolymer of fluorine-containing acrylate and polysiloxane, with a molecular weight of 5000-10000 g / mol and a fluorine content of 15-25 wt%.
3. The thermoplastic elastomer material according to claim 1, characterized in that, The white oil is a mixture of n-isoalkanes C16-C31 with a viscosity range of 10-70 mm 2 / s.
4. The thermoplastic elastomer material according to claim 1, characterized in that, The biodegradable polyester comprises polybutylene adipate terephthalate; and the natural antioxidant comprises one or more of tea polyphenol and vitamin E.
5. The thermoplastic elastomer material according to claim 1, characterized in that, The preparation method of the antibacterial component comprises the following steps: 1) ultrasonic dispersion of nano zinc oxide particles in an ethanol aqueous solution, addition of a silane coupling agent for reaction to obtain modified nano zinc oxide particles; dissolution of the modified nano zinc oxide particles in an ethanol-ammonia aqueous solution, and dropwise addition of tetraethyl orthosilicate for reaction to obtain ZnO@mesoporous SiO2core-shell powder; and 2) dissolution of ε-polylysine in a phosphate buffered saline solution, and addition of the ZnO@mesoporous SiO2core-shell powder for reaction to obtain ZnO@mesoporous SiO2core-shell structure loaded with ε-polylysine.
6. The thermoplastic elastomer material according to claim 5, characterized in that, In the ethanol aqueous solution of step 1), the volume ratio of ethanol to water is 3:1; and in the ethanol-ammonia aqueous solution of step 2), the concentration of ammonia water is 0.5 mol / L.
7. Thermoplastic elastomer material according to any of claims 1 to 6, characterized in that The poly(N-isopropyl acrylamide) microgel has a particle size of 50-200 nm and a phase transition temperature of 32-37℃.
8. A process for the preparation of a thermoplastic elastomeric material as claimed in any one of claims 1 to 7, characterised in that, The method comprises the following steps: (1) Pre-mixing: mixing styrene-ethylene-butylene-styrene block copolymer, biodegradable polyester, cellulose nanocrystal, and white oil in a mixer to obtain a pre-mixed rubber compound; (2) Dynamic vulcanization: adding the pre-mixed rubber compound, polypropylene, maleic anhydride grafted polypropylene, and poly(N-isopropyl acrylamide) microgel into a twin-screw extruder for dynamic vulcanization by controlling the temperature in different sections; (3) Functional additive blending: ultrasonic dispersion of the antibacterial component, fluorosilicon modified acrylate, and natural antioxidant, and injection of the dispersion into the end of the twin-screw extruder through a side feeding port for blending with the matrix; (4) Extrusion of the blended material obtained in step (3) through a die, water cooling, granulation, and drying to obtain thermoplastic elastomer particles.
9. The method of preparing a thermoplastic elastomer material according to claim 8, characterized in that, In step (2), the crosslinking agent for dynamic vulcanization is dicumyl peroxide, and the amount used is 0.1-0.3% of the mass of the styrene-ethylene-butylene-styrene block copolymer, and the vulcanization degree is controlled at 30-50%.
10. The method of preparing a thermoplastic elastomer material according to claim 8, characterized in that, In step (2), the temperature control in different sections is 170-175℃ in the first section, 180-185℃ in the second section, and 175-180℃ in the third section, the screw rotation speed is 250-350 rpm, and the dynamic vulcanization time is 3-5 min.